GuideYourSteps@CyprusTrails: δημιουργία διαδραστικής υπηρεσίας για τα μονοπάτια της Κύπρου και τα χαρακτηριστικά τους - Φλωρίδη, Θεανώ (Τμήμα Πολιτικών Μηχανικών και Μηχανικών Γεωπληροφορικής, Σχολή Μηχανικής και Τεχνολογίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2017)
This thesis deals with the creation of a service that includes all the nature paths of Cyprus and their relevant information. While many people interested, there has been little action to promote this activity in Cyprus. It is therefore necessary to organize and properly manage the paths for nature protection and to avoid anthropogenic impacts. Using the Web AppBuilder for ArcGIS an integrated service will be created to serve the hikers and attract sports tourism and nature lovers. Geographic Information Systems will be used to provide important information.
Keywords: Service; GIS; Navigation; Hiking; Paths; Διαδραστική υπηρεσία; Πλοήγηση; Πεζοπορία; Μονοπάτια